Biomimetic Growth of Hydroxyapatite on Electrospun CA/PVP Core–Shell Nanofiber Membranes - Hou, Jiazi (Polymers (Basel), 2018)
In this study, cellulose acetate (CA)/polyvinylpyrrolidone (PVP) core–shell nanofibers were successfully fabricated by electrospinning their homogeneous blending solution. Uniform and cylindrical nanofibers were obtained when the PVP content increased from 0 to 2 wt %. Because of the concentration gradient associated with the solvent volatilization, the composite fibers flattened when the PVP increased to 5 wt %. Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) results confirmed the existence of a hydrogen bond between the CA and PVP molecules, which enhanced the thermodynamic properties of the CA/PVP nanofibers, as shown by differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) results. To analyze the interior structure of the CA/PVP fibers, the water-soluble PVP was selectively removed by immersing the fiber membranes in deionized water. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) indicated that the PVP component, which has a low surface tension, was driven to the exterior of the fiber to form a discontinuous phase, whereas the high-content CA component inclined to form the internal continuous phase, thereby generating a core–shell structure. After the water-treatment, the CA/PVP composite fibers provided more favorable conditions for mineral crystal deposition and growth. Energy-dispersive spectroscopy (EDS) and FTIR proved that the crystal was hydroxyapatite (HAP) and that the calcium to phosphorus ratio was 1.47, which was close to the theoretical value of 1.67 in HAP. Such nanofiber membranes could be potentially applicable in bone tissue engineering.